Real time synthesis of digital automatic control systems for training - Baziukaitė, Dalia; Bielskis, Artūras (Lietuvos matematikos rinkinys, 2001)
The results of investigation of the digital automatic control systems with unitary negative feedback finding optimal serial links for their adjustment are discussed. Such links are useful optimizing system dynamics in real time, creating leaning programs and applying adaptation algorithms of the automatic control systems.